Enfermedad pulmonar obstructiva crónica (EPOC). Parte II: tratamiento - Ruiz C., Mauricio (Revista Hospital Clínico Universidad de Chile, 2008)
EPOC is a chronic irreversible illness capable of seriously damaging the quality of life, once confirmed the diagnosis, the treatment should be standardized. It proposes a phased approach to the treatment program that includes a withdrawal of smoking. The short-acting bronchodilators are listed as symptomatic therapy, the action long have been associated with a decrease in the number of exacerbations, so it can be used in moderate and severe COPD. The use of glucocorticoids inhalation is justified in severe COPD with more than three exacerbations per year. The chronic home oxygen therapy increases life expectancy in patients with stable hypoxemia, especially if they report an cor pulmonale. In the case of exacerbation of COPD is important to assess the need for hospitalization, if necessary, in addition to bronchodilator therapy should be added antibiotics and corticosteroids